A Potential Waste to be Selected as Media for Metal and Nutrient Removal. Issue 1 (July 2016) - Zayadi, N; Othman, N; Hamdan, R
Abstract: This study describes the potential of application of cassava peel, banana peel, coconut shell, and coconut coir to be selected as metal removal while limestone and steel slag for nutrient removal. The media were characterized by X-Ray Fluorescence (XRF), Fourier Transform Infrared (FTIR), Field Emission Scanning Electron Microscopy-Energy Dispersive X-Ray (FESEM-EDX), and X-Ray Powder Diffraction (XRD). The results of XRF analysis medias show the present of calcium oxide, CaO which confirm the high efficiency in adsorbing metal ions and nutrient which is in agreement with the result of XRD. The characteristics of medias by FTIR analysis also confirmed the involvement of alcohol, carboxylic, alkanes, amines and ethers which play important role to reduce ions while FESEM-EDX indicates the porous structures of study medias. The characterization analysis highlight that cassava peel and steel slag were selected as a potential media in this study.